Edukasi Hukum dan Pendampingan Standardisasi Sistem Pelepasan Informasi Rekam Medis Guna Menjamin Kerahasiaan Data Pasien di RSU Imelda Pekerja Indonesia - Abdul Malik Ritonga; Geovani Arta sihite; Zulham Andi Ritonga; Mei Sryendang Sitorus; Sarida Surya Manurung (Jurnal Masyarakat Indonesia (Jumas), 2026)
The release of medical record information to third parties carries significant legal risks regarding patient data confidentiality if not managed through rigorous verification procedures. This community service program (Pengabdian kepada Masyarakat) aimed to address legal vulnerabilities in the medical record release system at the Medical Record Unit of RSU Imelda Pekerja Indonesia. Using a Participatory Action Research (PAR) approach, the program engaged four medical record personnel through four main stages: situation analysis, solution development, legal education with practical coaching, and program evaluation. The interventions included legal socialization regarding Law No. 27 of 2022 on Personal Data Protection and Minister of Health Regulation No. 24 of 2022, as well as the implementation of a new verification tool, the Check-List for Verification of Medical Information Release Legitimacy (CV-PIM), along with an updated Standard Operating Procedure (SOP). The results demonstrated a 67.6% increase in personnel's legal literacy, with average test scores rising from 52.5 to 88.0. Furthermore, compliance with verification checklists reached 100%, and the application of data minimization principles increased by 375%. In conclusion, the implementation of a standardized release system effectively mitigates legal risks for healthcare personnel while ensuring sustainable protection of patient health data privacy at RSU Imelda Pekerja Indonesia.